Temperature phased anaerobic digestion at the intermediate zone of 45 ℃ : performances, stability and pathogen deactivation - Nuruol Syuhadaa Mohd; Li, Baoqiang; Shaliza Ibrahim; Rumana Riffat (Penerbit Universiti Kebangsaan Malaysia, 2021)
Temperature phased anaerobic digestion (TPAD) systems with conventional sequences (first stage of 55 ℃ and second stage of 35 ℃) have been widely studied. However, very limited studies were available on TPAD system with the first stage operated at the intermediate zone of 45 °C, mainly due to the notion that limited microbial activity occurs within this zone. The objective of this research was to evaluate the performance, stability and the capability of 45 °C TPAD in producing class A biosolids, in comparison to a conventional TPAD. Four combinations of TPAD systems were studied, 45 ℃ TPAD 2.5/10 (1st stage solids retention time (SRT) 2.5 days/2nd stage SRT 10 days), 45 ℃ TPAD 7.5/10, 55 ℃ TPAD 2.5/10 and 55 ℃ TPAD 7.5/10. Among all, 45 ℃ TPAD 7.5/10 was found to have the best performances, attributed to its high volatile solids (VS) destruction (58%), minimal acetate accumulation (127 mg/L), high methane yield (0.58 m3 CH4/kg VS removed), high COD destruction solid COD (sCOD; 74% and total COD (tCOD) 54%) and minimal free NH3 content (67.5 mg/L). As for stability, stable pH distribution, high alkalinity content and low VFA to alkalinity ratio, indicated a well-buffered system. Additionally, the system had also able to produce class A biosolids. Therefore, proved that TPAD system operated at the intermediate zone of 45 ℃ can perform better than the conventional TPAD, hence, highlighting its economic advantage.